Source strength assay of iodine‐125 seeds sealed within sterile packaging. (4th March 2013) - Otani, Yuki; Yamada, Takahiro; Kato, Shingo; Shikama, Naoto; Funakoshi, Kazuto; Kuroda, Isao; Numasaki, Hodaka; Nose, Takayuki; Dokiya, Takushi; Oguchi, Masahiko
Abstract : Early‐stage prostate cancer is widely treated by iodine‐125 (I‐125) seed implantation. While quality assurance methods are in place to assure consistency in I‐125 seed source strength, current methods involve the breaking of the sterilization package, raising issues concerning sterility and time limitations. The purpose of this study was to develop a method of characterizing the total source strength of I‐125 seeds within a cartridge that has been sealed within a sterilization package and to evaluate the probability of detecting an out‐of‐calibration seed (aberrant seed). We defined a protocol to determine the ability of a well‐type ionization chamber to detect aberrant I‐125 seeds within a cartridge sealed in the sterilization package. A novel jig for a well‐type ionization chamber was designed to accommodate the sterilization package. One seed was chosen randomly from two cartridges containing five or 15 seeds (0.544 U source strength) and was exchanged with aberrant seeds of six different source strengths. The source strength was measured at each position within the cartridge. The results indicated that the response of the well chamber was sensitive to changes in the aberrant seed position within the cartridge and the source strength of the aberrant seed. The correlation coefficient between single seed and batch assay results was high (0.998). A novel jig and a measurement method using a well ionization chamber were developed, which allowed for a batch assay characterization of the total source strength of I‐125 seeds within a cartridge sealed within sterilization package. This method is simple, time‐saving, and offers greater practical application. PACS number: D6.20.Dk